Enhancing Pancasila and Citizenship Education (PPKn) Learning Outcomes Through Classroom Action Research and Audio Media Integration - Afrida Erayani; Ester Julinda Simarmata; Rosdiana Samosir (Departement of Mathematics Education, 2024)
This action research intends to evaluate the impact of utilizing audio media in the teaching of Pancasila and Citizenship Education (PPKn) on students' learning outcomes. The study involved 30 students and applied a Classroom Action Research (CAR) approach to examine the effectiveness of integrating audio material in the instructional process. The data demonstrate a considerable improvement in individual and classical learning accomplishment during the second cycle. Individual proficiency grew from 15 to 18 students, while the classical proficiency rate rose from 75% to 90%. The average learning outcomes also showed a considerable improvement, with the average score climbing from 60.135 in the first cycle to 77.4 in the second cycle. This resulted in an overall improvement of 28.61% between the two periods. The research underlines the positive influence of audio media on boosting students' learning and accomplishment in PPKn. The study reveals that audio media can be a valuable tool in overcoming the obstacles experienced in teaching this subject, delivering a more interesting and effective learning experience for students. However, it is necessary to understand the study's limitations, such as the relatively small sample size and the focus on a single patient. Future study with bigger and more diverse samples could provide a more comprehensive knowledge of the broader applicability of audio media in educational contexts. In conclusion, the use of audio media in PPKn instruction constitutes a positive step toward increasing student learning outcomes. This research contributes to the educational literature and creates options for further inquiries into the incorporation of technology in learning contexts